(untitled) (Fiep Bulletin - online, 2014)
The performance of the motor abilities involves a muscular organization that the person allows to reach the goal of the ability that is being played. In the first periods of training of development, the interaction between the human being and the way occurs through movements, first through the stability, in second through the locomotion and in third through the manipulation, these being able to be evaluated through the static balance and dynamic, of the agility and the specific motricidade, respectively (GALLAHUE; OZMUN, 2001). Objective: To verify the profile of the motor abilities of visitors’ children of area of leisure located in zone west of the city of Rio de Janeiro. Methodology: The study it was descriptive type data-collecting, the sample was composed for 122 children being 58 of feminine gender and 64 of the masculine gender. For the evaluation extracted specific tests of the Test of Motor Proficiency of Bruininks-Oseretsky had been used (1974). Results: It was verified that the girls had presented better punctuations in all the carried through tests of that the boys. With relation (1) to the motor coordination it has an ample variation in both the sorts being that the best punctuations are observed to the 07 years-old in the group of the girls and to the 13 years-old in the one of the boys; (2) to the agility, it in such a way has a gradual decline in the group of the girls how much in the boys, with exception to the 13 years-old in the girls, where if it observes a fast increase in the average in relation to the 12 years-old; e, (3) balance, verified a gradual increase in the punctuations tending to the stabilization for return of the 9-10 years. Conclusions: The performances in the tests of this evaluated group show instability in the one in the punctuations gotten with relation to the coordination in the girls, a decrease in the agility until os14 years-old. With relation to the boys reduction of the agility occurs, increase of the coordination, except the 14 years, and gradual increase tending to the stability in the balance.